Consumer taste tests and milk preference in low-income, urban supermarkets. Issue 8 (16th September 2014) - Weiss, Stephanie; Davis, Erica; Wojtanowski, Alexis C; Foster, Gary D; Glanz, Karen; Karpyn, Allison
Abstract: Objective: To explore shoppers' responses to the taste of different types of cow's milk in a blind taste test and to examine their willingness to purchase lower-fat milk as part of an in-store marketing intervention. Design: Participants were recruited on-site in the supermarket to participate in a blind taste test of three varieties of cow's milk and asked to guess what type they sampled. Setting: The taste testing was conducted as part of the Healthy Retail Solution (HRS) intervention that took place in four large supermarkets in Philadelphia, PA, USA over the course of six months. Subjects: Adults ( n 444) at participating Philadelphia supermarkets. Results: The majority of participants at all stores reported typically purchasing higher-fat milk. Forty per cent of participants reported buying whole milk, 38 % purchased milk with 2 % fat. Very few participants correctly identified all three milk samples during the taste test (6·9 %) and a majority of participants were unable to identify the type of milk they self-reported typically purchased. Conclusions: Most consumers could not accurately distinguish between various types of milk. Taste testing is a promising strategy to introduce lower-fat milks to consumers who have not tried them before. Campaigns to purchase skimmed, 1 % or 2 % milk may result in significant energy reduction over time and can serve as a simple way to combat overweight and obesity.